Ultra-trace level determination of neonicotinoids in honey as a tool for assessing environmental contamination. (April 2019) - Kammoun, Souad; Mulhauser, Blaise; Aebi, Alexandre; Mitchell, Edward A.D.; Glauser, Gaétan
Abstract: Neonicotinoids and the closely related insecticide classes sulfoximines and butenolides have recently attracted growing concerns regarding their potential negative effects on non-target organisms, including pollinators such as bees. Indeed, it is becoming increasingly clear that these effects may occur at much lower levels than those considered to be safe for humans. To properly assess the ecological and environmental risks posed by neonicotinoids, appropriate sampling and analytical procedures are needed. Here, we used honey as reliable environmental sampler and developed an unprecedentedly sensitive method based on QuEChERS and UHPLC-MS/MS for the simultaneous determination of the nine neonicotinoids and related molecules currently present on the market (acetamiprid, clothianidin, dinotefuran, flupyradifurone, imidacloprid, nitenpyram, sulfoxaflor, thiacloprid and thiamethoxam). The method was validated and provided excellent levels of precision and accuracy over a wide concentration range of 3–4 orders of magnitude. Lowest limits of quantification (LLOQs) as low as 2–20 pg/g of honey depending on the analytes were reached. The method was then applied to the analysis of 36 honey samples from various regions of the World which had already been analysed for the five most common neonicotinoids (acetamiprid, clothianidin, imidacloprid, thiacloprid and thiamethoxam) in a previous study. This allowed us to determine the long-term stability (i.e. up to 40 months) of these molecules in honey, both at room temperature and −20 °C. We found that the five pesticides were stable over a period of several years at −20 °C, but that acetamiprid and thiacloprid partially degraded at room temperature. Finally, we also measured the levels of dinotefuran, nitenpyram, sulfoxaflor and flupyradifurone and found that 28% of the samples were contaminated by at least one of these pesticides. Graphical abstract: Image 1 Highlights: Neonicotinoid insecticides may be harmful to non-target organisms already at sub-ppb levels. Available methods for their quantification in environmental complex matrices lack sensitivity. An ultra-sensitive method for the monitoring of all neonicotinoids in honey is presented. The method is applied to a selection of 36 samples from various locations of the World. An investigation of the long-term stability of neonicotinoids in honey is made. Abstract : Honey is used as a tool for assessing the contamination of the environment by neonicotinoids and related molecules.